A method to improve position accuracy for the dual-drive feed machines by state-dependent friction compensation. (July 2022) - Liu, Qi; Lu, Hong; Zhang, Xinbao; Zhang, Yongquan; Wang, Yongjing; Li, Zhangjie; Duan, Meng
Due to high stiffness and quick response, dual-drive feed machines (DDFMs) are widely used in many precision CNC machines. The tracking errors of the two feed drives directly determine the machines' accuracy. The performance of the position accuracy can be easily affected by the difference in the friction dynamic characteristics of the two axes. This paper proposes the state-dependent friction compensation (SFC) as an improved DDFMs error compensation method that can achieve better accuracy under unequal friction on the two feed drives. It is theoretically analyzed the influence of friction on the transmission stiffness of DDFMs. Moreover, the effects of time-varying factors (feed rates and mechanical structures) on the friction of dual axes are discussed. The innovation of the paper is that the SFC can adaptively take into account the influence of the variable dual-drive structure and feed rate on DDFMs' position accuracy, and the compensation method combined with cross-coupled strategy is suitable for general dual-drive structure. Simulation and experiment results show that the proposed method can effectively improve the synchronization accuracy and tracking accuracy in a variety of feed operations (different feed rates, starting, and reversing).